The inattentive on-screen reading: Reading medium affects attention and reading comprehension under time pressure. (February 2021) - Delgado, Pablo; Salmerón, Ladislao
Abstract: This study explored the influence of reading media and reading time-frame on readers' on-task attention, metacognitive calibration, and reading comprehension. One hundred and forty undergraduates were allocated to one of four experimental conditions varying on the reading medium (in print vs. on screen) and on the reading time-frame (free vs. pressured time). Readers' mindwandering while reading, prediction of performance on a comprehension test, and their text comprehension were measured. In-print readers, but not on-screen readers, mindwandered less on the pressured than in the free time condition, indicating higher task adaptation in print. Accordingly, on-screen readers in the pressured condition comprehended less than the other three groups. Mindwandering and text comprehension were similar under free reading time regardless of medium. Lastly, there were no differences in readers' metacognitive calibration. The results support the hypothesis of shallow information processing when reading on screen under time constraints. Highlights: On-print (but not on-screen) readers increased on-task attention when required by the task. On-screen (as compared to on-print) readers comprehended less when reading under time pressure. Readers were equally well calibrated regardless of reading medium and time pressure.